2013
DOI: 10.1097/prs.0b013e31827c6dc2
|View full text |Cite
|
Sign up to set email alerts
|

Fat Necrosis in Autologous Abdomen-Based Breast Reconstruction

Abstract: Although there is little agreement in the literature regarding risk factors for fat necrosis, the authors were able to demonstrate several significant predictors by systematically analyzing 70 articles. Improved knowledge of the risk factors for fat necrosis can help surgeons provide improved preoperative counseling and take measures to minimize the risk of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 53 publications
0
50
0
1
Order By: Relevance
“…Along similar lines, the presence of a small area of fat necrosis may not require intervention or might be resolved with simple liposuction, but fat necrosis can also sometimes lead to atrophy and contracture of the reconstructed breast. 17, 18, 32-34 Although not all fat necrosis identified in this study may have been clinically consequential, we do believe that the increased rate of this complication in radiated patients merits consideration, particularly because it can necessitate additional imaging, cause anxiety, and even require surgical intervention.…”
Section: Discussionmentioning
confidence: 80%
“…Along similar lines, the presence of a small area of fat necrosis may not require intervention or might be resolved with simple liposuction, but fat necrosis can also sometimes lead to atrophy and contracture of the reconstructed breast. 17, 18, 32-34 Although not all fat necrosis identified in this study may have been clinically consequential, we do believe that the increased rate of this complication in radiated patients merits consideration, particularly because it can necessitate additional imaging, cause anxiety, and even require surgical intervention.…”
Section: Discussionmentioning
confidence: 80%
“…40 A recent systematic review of the literature with 5059 DIEP flaps found a fat necrosis rate of 8.7% among patients with no history of irradiation, which was significantly lower than in patients who underwent pre-reconstruction (11%, p Z 0.022) and post-reconstruction irradiation (22.3%, p < 0.001). 43 However, a notable observation in existing literature is the division of opinion regarding the deleterious effects of radiation therapy on the outcome of free-flap breast reconstruction, and hence the differing preference in the timing of surgery in relation to PMRT.…”
Section: Discussionmentioning
confidence: 98%
“…Inclusion criteria were English-language publication, human subjects, ear reconstruction, extractable outcomes on complications, and full-text availability. Exclusion criteria were systematic reviews and meta-analyses, case reports and case series with fewer than 15 patients, and nonrelated with surgery (the method is also provided in other systemic review about fat necrosis in autologous breast reconstruction by Khansa et al 2 ). Finally, 260 articles were excluded and 60 articles were reviewed and analyzed (Fig.…”
Section: Methodsmentioning
confidence: 99%